2017
DOI: 10.1007/s00423-017-1615-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic reversal of mini-gastric bypass to original anatomy for severe postoperative malnutrition

Abstract: Post-MGB SRMS and its related comorbidities are rare but dreaded conditions. Although burdened by a significant postoperative morbidity and weight regain, RMGB remains an effective option to consider, when intensive nutritional support fails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 28 publications
1
42
0
1
Order By: Relevance
“…One area of specific concern following MGB-OAGB revision was the potential for jejunal stenosis at the previous GJ site. Genser et al [23] reported increased risk of jejunal stenosis following horizontal division of the GJ anastomosis without resection of the jejunal loop. They found that this could be ameliorated with resection of the jejunal section at risk and performing a primary anastomosis of the two resected ends.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One area of specific concern following MGB-OAGB revision was the potential for jejunal stenosis at the previous GJ site. Genser et al [23] reported increased risk of jejunal stenosis following horizontal division of the GJ anastomosis without resection of the jejunal loop. They found that this could be ameliorated with resection of the jejunal section at risk and performing a primary anastomosis of the two resected ends.…”
Section: Discussionmentioning
confidence: 99%
“…Reversal to original anatomy following MGB-OAGB was considered a technically more challenging option, involving two primary steps: (1) reestablishment of continuity between gastric pouch and remnant stomach via gastro-gastrostomy (GG) and (2) reversal of prior established GJ. Genser et al [23] had reported the largest case series (n = 26) of this surgical technique. To restore the original gastric anatomy, a linear endostapler was used to create GG anastomosis.…”
Section: Revision To the Original Anatomymentioning
confidence: 99%
“…На даний час існує настороженість щодо нутритивної недостатності після міні-шунтування, яка недостатньо описана в літературі. Існують повідомлення про повторні оперативні втручання з приводу дефіцитних станів [13,21,23].…”
Section: вступunclassified
“…Revisions for complications have been reported in about 1%–2% patients for GERD,[ 9 10 11 ] 0%–2% for MUs,[ 6 12 ] 0%–1.01% for severe malnutrition, and about 0.5% for incomplete weight loss and weight regain. [ 1 5 6 11 12 13 14 15 16 17 ]…”
Section: Introductionmentioning
confidence: 99%